Ladybugs - Watts, Barrie (Franklin Watts New York, 1990)
Discusses the feeding and reproductive habits of ladybugs and suggests ways to raise and breed them domestically.
8 - 10 years
Keywords: Ladybirds as pets -- Juvenile literature; Ladybirds -- Juvenile literature; lady bugs; Ladybugs -- Collection and preservation